Observational constraints on the new generalized Chaplygin gas model - Liao, Kai; Pan, Yu; Zhu, Zong-Hong (Research in astronomy and astrophysics, 2013)
We use the latest data to investigate observational constraints on the new generalized Chaplygin gas （NGCG） model. Using the Markov Chain Monte Carlo method, we constrain the NGCG model with type Ia supernovae from the Union2 set （557 data）, the usual baryonic acoustic oscillation （BAO） observation from the spectroscopic Sloan Digital Sky Survey data release 7 galaxy sample, the cosmic mi- crowave background observation from the 7-year Wilkinson Microwave Anisotropy Probe results, newly revised data on H（z）, as well as a value of θBAO （Z = 0.55） = （3.90° ±0.38°） for the angular BAO scale. The constraint results for the NGCG model are ωX=-1.0510＋0.1563-0.1685（1σ）＋0.2226-0.2398（2σ）,η=1.0117＋0.0469-0.0502（1σ）＋0.0693-0.0716（2σ）and ΩX=0.7297＋0.0229-0.0276（1σ）＋0.0329-0.0402（2σ）, which give a rather stringent constraint. From the results, we can see that a phantom model is slightly favored and the proba- bility that energy transfers from dark matter to dark energy is a little larger than the inverse.